Physics-Based SPICE-Compatible Compact Model of FLASH Memory With Poly-Si Channel for Computing-in-Memory Applications - Jung Rae Cho; Donghyun Ryu; Donguk Kim; Wonjung Kim; Yeonwoo Kim; Changwook Kim; Yoon Kim; Myounggon Kang; Jiyong Woo; Dae Hwan Kim (IEEE Journal of the Electron Devices Society)
Recently, three-dimensional FLASH memory with multi-level cell characteristics has attracted increasing attention to enhance the capabilities of artificial intelligence (AI) by leveraging computingin-memory (CIM) systems. The focus is to maximize the computing performance and design FLASH memory suitable for various AI algorithms, where the memory must achieve a highly controllable multi-level threshold voltage (VT). Therefore, we developed a SPICE compact model that can rapidly simulate charge trap FLASH cells for CIM to identify optimal programming conditions. SPICE simulation results of the transfer characteristics are in good agreement with the results of experimentally fabricated FLASH memory, showing a low error rate of 10%. The model was also validated against the results obtained from the TCAD tool, showing that a consistent VT change was computed in a shorter time than that required using TCAD. Then, the developed model was used to comprehensively investigate how single or multiple gate voltage (VG) pulses affect VT. Moreover, considering recent FLASH memory fabrication processes, we found that grain boundaries in polycrystalline silicon channel materials can be involved in deteriorating gate controllability. Therefore, optimizing the pulse scheme by correcting potential errors identified in advance through fast SPICE simulation can enable the accurate achievement of the specific analog states of the FLASH cells of the CIM architecture, boosting computing performance.